2016
DOI: 10.3847/1538-4357/833/1/45
|View full text |Cite
|
Sign up to set email alerts
|

Deriving the Properties of Coronal Pressure Fronts in 3d: Application to the 2012 May 17 Ground Level Enhancement

Abstract: We study the link between an expanding coronal shock and the energetic particles measured near Earth during the ground level enhancement of 2012 May 17. We developed a new technique based on multipoint imaging to triangulate the three-dimensional (3D) expansion of the shock forming in the corona. It uses images from three vantage points by mapping the outermost extent of the coronal region perturbed by the pressure front. We derive for the first time the 3D velocity vector and the distribution of Mach numbers,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
161
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(179 citation statements)
references
References 84 publications
(146 reference statements)
17
161
0
Order By: Relevance
“…Here, there is a significant difference with the previous OCBF, in that a large patch of high-u BN values close to the flanks of the OCBF develops over time, including many open field line crossings. Similar patches, or 'valleys' of quasi-perpendicularity were previously discussed by Kozarev et al (2015) and Rouillard et al (2016), and could mean that efficient particle acceleration may take place along a long linear structure on the shock surface. The nominal connectivity to Earth throughout the event is very good, and increases, as well as the spread of connected field lines (panels G and H).…”
Section: December 12 2013 Eventmentioning
confidence: 75%
“…Here, there is a significant difference with the previous OCBF, in that a large patch of high-u BN values close to the flanks of the OCBF develops over time, including many open field line crossings. Similar patches, or 'valleys' of quasi-perpendicularity were previously discussed by Kozarev et al (2015) and Rouillard et al (2016), and could mean that efficient particle acceleration may take place along a long linear structure on the shock surface. The nominal connectivity to Earth throughout the event is very good, and increases, as well as the spread of connected field lines (panels G and H).…”
Section: December 12 2013 Eventmentioning
confidence: 75%
“…It has been shown that in the 2012 May 17 GLE event, the first in solar cycle 24, the CME shock originated below a streamer and the streamer magnetic configuration strongly affects the obliquity of the shock as it moves outward (Rouillard et al 2016). To better understand the physical connection between large SEP events and CME/shock-streamer interactions, the large-scale magnetic configuration in the CME shock initiation region should be examined for more events.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recently, Rouillard et al (2016) showed that the CME shock of the GLE event on 2012 May 17 originated below a streamer, indicating that the large-scale magnetic configuration of streamers may also affect SEP acceleration at coronal shocks. However, due to the limited capability of current imaging observations of CME -streamer interaction in the corona, and the unavailability of direct measurement of coronal magnetic field topology, the role of streamers or CME-streamer interaction in the acceleration, trapping, and release of energetic particles remains unclear (see, e.g., Kahler et al 2000;Kahler & Vourlidas 2005;Rouillard et al 2016;Kocharov et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing amount of evidence for the association of CME-driven shocks with SEPs in the corona (see recent papers, e.g., Rouillard et al, 2012Rouillard et al, , 2016Carley et al, 2013;Lario et al, 2014Lario et al, , 2016Salas-Matamoros et al, 2016, and references therein) but it remains unclear whether such shock waves are capable of accelerating particles at the observed energies Mancuso, 2010, 2011). An important shock parameter that could be accessible from coronagraphic observations is the ratio between the downstream and upstream electron densities or density compression ratio, X.…”
Section: Introductionmentioning
confidence: 99%